An exploratory analysis of Title II equity crowdfunding success. Issue 3 (3rd July 2017) - Mamonov, Stanislav; Malaga, Ross; Rosenblum, Janet
Abstract: The passage of the Jumpstart Our Business Startups Act (JOBS Act) ushered in a new wave of equity crowdfunding in the United States. Title II of the JOBS Act aims to make it easier for new ventures to raise funds from accredited investors. The number of Title II crowdfunded projects is growing rapidly. Based on data for US online 506(c) offerings across 17 leading platforms, more than 1.49 billion in capital was committed to Title II projects through May 2016. Our analysis of Title II offerings from these platforms reveals that real estate ventures are the single largest category with more than 383 million in committed capital, yet only 50% of the crowdfunded real estate offerings reach the full amount of the requested capital. Text mining of the real estate project descriptions reveals the critical facilitation role played by the successful crowdfunding platforms in reducing the information asymmetry between the entrepreneurs and investors by performing due diligence on the potential Title II investment opportunities.